Pendekatan Fenomenologi Dalam Penciptaan Kriya - Guntur Guntur (Institut Seni Indonesia Surakarta, 2008)
There are two things need to be considered when wewill discuss about the problem of work creation methodology.Firstly, the one relates to the paradigmatic aspect ofwork. Secondly, the implication of work paradigm will influencevarious probabilities of approach adoption and methodology.The two fundamental things need to be proposed asthe topic of discussion in order to obtain the clarity of positionin determining or adopting the methodology referred inartistic creation process, including in the work area. Thepaper is concluded with a proposal of phenomenological approachas the alternative in the work creation.Keywords: Work, Phenomenology